PENGARUH PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP PEMAHAMAN KONSEP DAN BERPIKIR LOGIS SISWA - Nur Sri Widyastuti; Pratiwi Pujiastuti (Jurnal Prima Edukasia, 2014)
Penelitian ini bertujuan untuk (1) mengetahui pengaruh penggunaan Pendidikan Matematika Realistik Indonesia (PMRI) dan Direct Instruction (DI) dalam pembelajaran matematika materi jarak dan kecepatan terhadap: pemahaman konsep dan berpikir logis Siswa, (2) mengetahui pengaruh positif pembelajaran matematika dengan PMRI terhadap pemahaman konsep siswa, dan (3) mendeskripsikan pengaruh positif pembelajaran matematika dengan PMRI terhadap berpikir logis. Populasi penelitian adalah siswa kelas V segugus II Kecamatan Umbulharjo dengan sampel 3 sekolah dengan subjek penelitian 91 siswa. Instrumen yang digunakan adalah tes pemahaman konsep dan berpikir logis awal maupun akhir. Analisis data yang digunakan adalah uji multivariat of covariance (MANCOVA), kemudian dilanjutkan dengan independent sample t-test dengan taraf signifikansi 0,05. Hasil penelitian ini menunjukkan bahwa: (1) terdapat pengaruh yang signifikan antara pembelajaran matematika dengan PMRI dan DI dalam pembelajaran matematika materi jarak dan kecepatan terhadap pemaham-an konsep dan berpikir logis siswa, (2) terdapat pengaruh positif pembelajaran matematika dengan PMRI terhadap pemahaman konsep siswa daripada Direct Instruction (DI), dan (3) terdapat pengaruh positif pembelajaran matematika dengan PMRI terhadap berpikir logis siswa daripada Direct Instruction (DI) bagi siswa kelas V Sekolah Dasar segugus II Kecamatan Umbulharjo Kota Yogyakarta.THE EFFECTS OF REALISTIC MATHEMATICS EDUCATION INDONESIA (PMRI) ON UNDERSTANDING CONCEPTS AND LOGICAL THINKING STUDENTSABSTRACTThis research aimed to (1) know the effect of the use of Realistic Mathematics Education in Indonesia (PMRI) and Direct Instruction (DI) on the subject of distance and speed of the: Understanding the concept and Logical Thinking students, (2) know the positive influence effect of the use of Realistic Mathematics Education in Indonesia (PMRI) of the Understanding the concept, and (3) describe the positive influence effect of the use of Realistic Mathematics Education in Indonesia (PMRI) of the logical thingking students. The population of the study was students in the V class group 2 District of Umbulharjo with sampling selected three classes using with 91 subject students. Class experiments were treated using PMRI learning and classroom learning control with Direct Instruction (DI). Data collection techniques used are testing techniques to determine the ability of Understanding Concepts and Logical Thinking students on the subject of distance and speed after treatment. The data analysis technique used is the multivariate test of covariance (MANCOVA), followed by independent sample t-test with a significance level of 0.05. The results of this study indicate that (1) there are significant differences in the learning of mathematics with PMRI and DI in mathematics learning material to distance and speed of the: understanding of the concept and logical thinking students, (2) Learning math using PMRI gives more positive effect on the understanding concepts of students rather than using Direct Instruction, and (3) Learning math using PMRI gives more positive effect on the logical thinking of students rather than using Direct Instruction for Fifth Grade Group 2 Elementary School Umbulharjo District of Yogyakarta.Keywords: mathematics learning, PMRI, direct instruction, understanding concepts, logical thinking